A Study About the Optimum Capacity for Brick Industry in Kanyakumari District - Wilson, M.; Devi, C. Mallika (Indian Journal of Marketing, 2007)
Brick making is a traditional, unorganized industry, generally confined to rural and peri-urban areas. Bricks have been used for shelter and protection for many thousands of years. Applications of brick included thick, often decorated work in large multi-storey buildings, arches, jambs and other work in predominantly stone walls, domestic walling and infill in stud partitions.